Slovenski podjetniški observatorij 2002. (1. del) - Rebernik, Miroslav; Močnik, Dijana; Rus, Matej (2002)
Slovenian Entrepreneurship Observatory 2002. (Part 1). The publication Slovenian Entrepreneurship Observatory 2002 provides an overview of the state of Slovenian entrepreneurship in 2000 and its comparison with Europe-19. Research has shown that the number of companies and percentage of employees in each size class is comparable with the EU-19, but that the economic power of Slovenian entrepreneurs is rather weak. The average value added per employee in the EU - 19 amounted to EUR 80,000 euros, while in Slovenia only 19,000 euros. A comparison between the average income created and value added is reflected in the highly expenditure wastefulness of Slovenian entrepreneurship. While the relationship between the average revenue per company in Slovenia and the EU-19 amounts to 1: 2.75, the value added per employee ratio is already 1: 4.21. This difference is largest for medium-sized companies, reaching only 17% of the value added, as generated by medium-sized European companies (18,000 euros to 105,000 euros).
Keywords: podjetništvo; podjetniška demografija; EU-19; primerjalna analiza; mala in srednje velika podjetja; Business demography; Comparative Analysis; Small and Medium-Sized Enterprises